Joe Sacco in literarno novinarstvo v podobi stripa - žanrski preplet literature, stripa, novinarstva in zgodovine - Flis, Leonora (Primerjalna književnost, 2014)
The article disusses the work of a comics artist-literary journalist Joe Sacco. Literary journalism in the form of graphic novels is a type of narrative that combines objective descriptions of empirical reality with more subjective visual representations and first-person testimonies of the author and of eyewitnesses of a depicted event or situation. The essay predominantly illuminates Sacco's portrayal of the Middle Eastern crisis, as exposed in his graphic books Footnotes in Gaza (2009) and Palestine (1996).
Keywords: Sacco, Joe, 1960-; literarno novinarstvo; žanrski hibridi; hibridni žanri; reportažni strip